MicroRNAs as the critical regulators of Cisplatin resistance in ovarian cancer cells - Meysam Moghbeli (BMC, 2021)
Abstract Background Ovarian cancer (OC) is one of the leading causes of cancer related deaths among women. Due to the asymptomatic tumor progression and lack of efficient screening methods, majority of OC patients are diagnosed in advanced tumor stages. A combination of surgical resection and platinum based-therapy is the common treatment option for advanced OC patients. However, tumor relapse is observed in about 70% of cases due to the treatment failure. Cisplatin is widely used as an efficient first-line treatment option for OC; however cisplatin resistance is observed in a noticeable ratio of cases. Regarding, the severe cisplatin side effects, it is required to clarify the molecular biology of cisplatin resistance to improve the clinical outcomes of OC patients. Cisplatin resistance in OC is associated with abnormal drug transportation, increased detoxification, abnormal apoptosis, and abnormal DNA repair ability. MicroRNAs (miRNAs) are critical factors involved in cell proliferation, apoptosis, and chemo resistance. MiRNAs as non-invasive and more stable factors compared with mRNAs, can be introduced as efficient markers of cisplatin response in OC patients. Main body In present review, we have summarized all of the miRNAs that have been associated with cisplatin resistance in OC. We also categorized the miRNAs based on their targets to clarify their probable molecular mechanisms during cisplatin resistance in ovarian tumor cells. Conclusions It was observed that miRNAs mainly exert their role in cisplatin response through regulation of apoptosis, signaling pathways, and transcription factors in OC cells. This review highlighted the miRNAs as important regulators of cisplatin response in ovarian tumor cells. Moreover, present review paves the way of suggesting a non-invasive panel of prediction markers for cisplatin response among OC patients.